Objektifikasi Perempuan dalam Cerpen Lipstik Karya Seno Gumira Ajidarma - W Winarti (UIN Raden Mas Said Surakarta, 2020)
The objectification of women has been perpetuated from time to time, generation to generation, in various forms, even in a very subtle form so that women do not feel that their bodies have been reduced into something passive, no more than a gender object, dwelling to sexual desire and exploitation of womenâ€™s bodies. In Indonesia, the writings presented by mass media have been conditioned into â€œmale patternsâ€. Besides mass media, the world of literature also recognizes women as a magnet of a story, in a short story or novel. This thing perpetuates womenâ€™s position as objects in literary works. The narrations about women in short stories and novels are constructed to fulfill the standards set by patriarchy through narrations about women. It is undeniable that male domination seems to have penetrated into womenâ€™s lives, even to the smallest things. Consciously or not, women always walk on the paths that have been set by men. In modern era like today, many women still stand under male domination as if they do not have the rights of themselves and their bodies. The narrations about objectification of women are found in Lipstik short story by Seno Gumira Ajidarma. In this short story, women are constructed to be passive objects, they are narrated as objects of oppression and body exploitation conducted by men.